Percutaneous Coronary Intervention for a Patient with Left Main Coronary Compression Syndrome - Ikegami, Ryutaro (Intern Med, 2018)
Left main coronary compression syndrome rarely occurs in patients with severe pulmonary hypertension. A 65-year-old woman with severe pulmonary hypertension due to an atrial septal defect suffered from angina on effort. Cardiac computed-tomography and coronary angiography revealed considerable stenosis of the left main coronary artery (LMA) caused by compression between the dilated main pulmonary artery trunk and the sinus of valsalva. Stenting of the LMA under intravascular ultrasound imaging was effective for the treatment of angina. We herein report the diagnosis and management of this condition with a brief literature review.